Chapter 1: Metals and Alloys, Materials Processing Technologies (Down Milling Cutting Parameters Optimization Utilizing the Two Level Full Factorial Design Approach) - Mohamed, Prof. Ts. Dr. Saiful Bahri; Musanih, Muhamad Ruzlan (Trans Tech Publications Ltd, 2016)
The directing of feeding the work piece and cutter rotation determines the type of machining mode either it is up milling or down milling. Each of this machining mode affects the quality of machined surface produced. This paper described the experimental design of won milling operation on a stack of multIdirectional CFRP/AI2024. There cutting paarmeter were considered namely, spindle speed (N), feed rate (fr) and depth of cut (dc). Two level full factorial design was utilized to plan systematic experimental methodology. Th analysis of variance (ANOVA) was used to analyse the influence and the interaction factors associated to surface quality. The results show that the depth of cut is the most significant factor for AI2024 and for CFRP the spindle speed and feed rate are significant. Surface roughness if CFRP is found to be at 0.594 um at the setting of N=117650 RPM,FR=750 mm/min and dc=0.255mm. Meanwhile for AI2024 the surface roughness is found to be at 0.32um. The validation test showed average deviation of predicted to actual value surface roughness is 3.11% for CFRP and 3.43% for AI2024.